The Role of the Court of Justice and National Courts in the EU Legal Protection System in the Context of the Organization of National Justice - AGNIESZKA KASTELIK-SMAZA (Zeszyty Naukowe Wyższej Szkoły Finansów i Prawa w Bielsku-Białej, 2022)
The study addresses the issue of judicial independence from the perspective of EU law. As the system of protection of rights conferred by EU law is dualistic in nature, apart from exceptional cases in which individuals have a locus standi in direct actions, they can only enforce their rights derived from EU law before the national courts. The Court of Justice is entitled to assess the way in which justice is structured in the Member States for the reason that the activity of the national courts is not of a purely domestic nature. These courts act at the same time as EU courts whose task is to ensure effective protection of the rights of individuals under EU law. The competence of the Court of Justice in the above area cannot be limited by the jurisprudence of national constitutional courts, especially if that jurisprudence refers to national constitutional identity or national sovereignty in order to justify non-compliance with EU law, leading in fact to a lowering of the standard of protection of fundamental rights, including the right to a fair trial.